The epistemological validity of suspicion and its impact on the evolution of human sciences - Naiemeh Najmi Nejad; Abdullah Mohammadi; Mustafa Hosseini Nesab, (حکمت اسرا)
One of the main topics in the science of the principles of suspicion, such as single news, the authority of appearances, etc. Most of the issues raised in the authenticity of suspicion are raised with a principled approach, and its epistemological value has been given less attention. The main problem of this article is to analyze this issue. This article, which is written with a descriptive-analytical method, expresses the views of Usulians on the validity of suspicion and then tries to find a way to explain the reality of suspicion, which according to the chosen point of view of this article, it is proved that these suspicions have discovery and reality. And the credibility of rational Emirates, including the news of Wahad, is not something outside of their essence, and they do not need to forge authenticity. In addition to opening a new path in explaining the validity of suspicion, proving the reality of suspicion has numerous benefits in non-jurisprudential descriptive sciences, especially humanities. Especially, this method can be used in the three areas of "existing human being", "ideal human being" and "transformation method from the existing situation to the desired situation".